PEMBELAJARAN PJOK BERBASIS PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) DI SMK N 8 SEMARANG - Nurratri, Rafika; Herlambang, Tubagus (Journal of Physical Activity and Sports (JPAS), 2024)
This study aims to analyze the implementation of the Culturally Responsive Teaching (CRT) approach in Physical Education, Sports, and Health (PJOK) learning at SMK N 8 Semarang. CRT is used to answer the challenges of cultural diversity of students, by integrating local cultural values in the learning process. The research method used is descriptive qualitative with data collection techniques in the form of observation, interviews, and documentation. The research population includes all PJOK teachers and students at SMK N 8 Semarang, as well as documents related to learning. The research sample consists of one PJOK teacher and students in a particular class that is the focus of the CRT approach. Learning documents such as the Lesson Implementation Plan (RPP), evaluation tools, and teaching materials were also analyzed. The sampling technique used purposive sampling to ensure the representation of subjects that are relevant to the research objectives. The results showed that PJOK teachers succeeded in integrating local cultural values in learning through traditional games, contextual discussions, and culture-based sports activities. Students responded positively to this approach, which created an inclusive and meaningful learning environment. This study contributes to the development of local culture-based PJOK learning practices in vocational high schools.